Pelaksanaan Pengawasan Inspektorat Daerah pada Organisasi Perangkat Daerah Kabupaten Batang Hari - Fauziah Fauziah; Yulia Istia Ningsih; Sumantri Sumantri (Universitas Batanghari, 2020)
The regional inspectorate functions as the internal auditor of the government which has the task of carrying out regional government general oversight activities and other tasks assigned by the regional head. In order to prevent the occurrence of irregularities and abuse of authority in the administration of government, in each government institution a government internal supervision institution is formed which specifically carries out the supervisory function. Government internal supervision institutions are institutions that are formed and internally are part of the government system that has the main tasks and functions in the field of supervision. The analytical method used in this research is descriptive qualitative method. This type of research used aims to obtain an overview and understanding and also explain how the supervision carried out by the Batang Hari Regional Inspectorate in the Batang Hari Regional Organization by basing on the results of observations, interviews, documentation, and literature studies. Based on the results of research conducted by the author of the Implementation of Supervision of Regional Inspectorate in the Regional Organization of the Batang Hari Regency, in general it has been implemented well, effectively and in accordance with the SOP, but there are still shortcomings, one of which is the timeliness in the issuance of the Audit Report.